Bosnia and Herzegovina : Financial Inclusion Technical Note - World Bank; International Monetary Fund (World Bank Group, Washington, DC, 2015)
This Technical Note was prepared in the context of a joint World Bank-IMF Financial Sector Assessment Program mission in Bosnia and Herzegovina during October-November 2014. Financial inclusion in Bosnia and Herzegovina performs relatively well compared to peers, but gaps remain for selected market segments. Financial sector development and access to finance for firms is constrained by weak domestic demand, high collateral requirements and inadequate credit enforcement mechanisms.